Chromosome studies in Argentinian species of Stemodia L. (Scrophulariaceae) - Sosa, María de las Mercedes (2002)
Chromosome studies were carried out on 5 Argentinian species of Stemodia. First chromosome counts are presented for S. ericifolia (2n=22), S. lanceolata (2n=22), S. stricta (2n=44) and S. hyptoides (2n=66), while the number 2n=22 of S. verticillata is confirmed. These numbers constitute the first reports for South American species of Stemodia. In addition, the karyograms of S. lanceolata and S. verticillata are the first descriptions for the genus. Diploid species showed regular meiotic behaviour and pollen viability was high in all the accessions analysed. These results suggest that 2 different mechanisms would be implicated in chromosome diversification of Stemodia. The first one implicates variation in genome size with karyotype formulae conservation and the second, polyploidy. Chromosome data provided here are discussed in relation to growth habit, morphological characters and taxonomic position of the species.